Analisis Laju Perkecambahan Kacang Tanah (Arachis hypogaea (L.) Merr.) yang Diberikan Kombinasi Perlakuan Suhu dan Lama Perendaman Asap Cair (Liquid Smoke) - Basry Yadi Tang; Stormy Vertygo; Abner Tonu Lema; Wahyu Dani Swari (Jurnal Penelitian Pertanian Terapan, 2020)
The research aims to get to analyze the effect of temperature and liquid smoke soaking combination on the velocity of peanut germination. Parameters measure were; Mean Germinatin Time (MGT), Mean Germinatin Rate (MGR), Final Germintaion Percentage (GT), Coefficient Velocity Of Germination (CVG), Germination Rate Index (GRI). The treatment combinations used were temperature 250C (1), 300C (2), 350C (3) dan 400C (4) and liquid smoke in which the seeds were soaked for 1 hour (a), 2 hours (b) and 3 hours (c). This resulted in 12 treatment combinations. Results showed that the best treatments were control 1 (K0 250C), control 4 (K0 400C) and 4a (K1 400C), with germination velocity as folows: 1.67 cm.day-1, 1.50 cm.day-1 and 2.00 cm.day-1 respectively . However, it is recommended to use soaking in liquid smoke for an hour (1a) in order to further initiate germination development that could hopefully lead to a much higher peanut crop yield during cultivation.